Evaluation of IT Governance in Indonesia's One-Door Investment and Integrated Services Institution using COBIT 5 - Satria, Wahyu Indra; Ilmi, Farwis; Indah Pratiwi, Nuning (Universitas Pendidikan Nasional, 2024)
This research aims to evaluate the information technology governance at Indonesia's One-Door Investment and Integrated Services Institution using the COBIT 5 framework. COBIT 5 is a comprehensive framework that provides a model for managing and governing information technology within an organization, to ensure the achievement of strategic and operational objectives. The research was conducted through several stages, including identifying relevant information technology processes, data collection through questionnaires and interviews, and analysis of the evaluation results using capability levels provided by COBIT 5 framework. The study results indicate that most information technology processes at Indonesia's One-Door Investment and Integrated Services Institution are at capability levels that require improvement, particularly in information technology risk management, performance management, and internal controls. Several recommendations are provided to enhance information technology governance at Indonesia's One-Door Investment and Integrated Services Institution, such as strengthening information technology policies and procedures, increasing human resource capacity through continuous training, and implementing regular monitoring and evaluation systems. By adopting these recommendations, it is expected that information technology governance at Indonesia's One-Door Investment and Integrated Services Institution can be optimized to support the achievement of organizational goals better and improve public services for the citizens.